Measurements of p53 Isoform Protein Concentration and Energetic Levels in Cells of CLL Using Enzymatic Methods - Udristioiu, Aurelian; Giubelan, Alexandru; Velcea, Ana; Martin, Liviu; Cojocaru, Manole; Gheorghe, Ioan-Ovidiu (International Journal of Innovative Research in Medical Science, 2025)
Background/Objectives: Aim of this works of researches proposed the detection of the isoform p53 protein in the patients with Chronic Lymphocytic Leukemia of type B, (CLL-B), performed using the quantitative sandwich Enzyme linked immunoassay ELISA for the direct detection of the p53 isoform protein, a product of the mutant P53 gene. Methods: Additionally, the cellular energy levels, particularly in CLL-B, were measured using a bioluminescence method. The study employed a quantitative sandwich ELISA method for the direct detection of the p53 isoform protein, a product of the mutant P53 gene Adenosine triphosphate, (ATP), was measured using the standard bioluminescence principle on an automatic LKB analyzer with an ATP monitoring reagent. Results: The presence of isoform p53 protein in the studied group was calculated at 17%. Unfavorable evolution and transformation of CLL into Diffuse Large B-Cell Lymphoma (DLBCL) were observed in 3.5% of the cases. In such as malignant diseases, increased ATP values were observed in Chronic Lymphatic Leukemia in values of 4.30-4.55 μM ATP, (Normal energy in B Cells: x̄ = 0.35 μM ATP, (SD = 0.42). Conclusion: Maturation state of the clonal tumor and the prognosis of patients with CLL depend on anaerobic metabolism and the expression of the p53 protein isoform.